Iron-dependent lysosomal dysfunction mediated by a natural product hybrid. Issue 7 (8th December 2015) - Mariani, A.; Mai, T. T.; Zacharioudakis, E.; Hienzsch, A.; Bartoli, A.; Cañeque, T.; Rodriguez, R.
Abstract : Marmycin A and artemisinin join forces as the molecular hybrid artesumycin, a new fluorescent lysosomotropic small molecule that targets lysosomal iron to kill cancer cells. Abstract : Artesumycin is a fluorescent hybrid of the natural products marmycin A and artemisinin. It was designed to combine the lysosomotropic properties of the angucycline and the iron-reactive capacity of the endoperoxide to target the lysosomal compartment of cancer cells. Herein, we show that artesumycin inhibits cancer cell proliferation in an iron-dependent manner and chemically fragments in vitro in the presence of redox-active iron(ii ). Visual detection of artesumycin by fluorescence microscopy provided substantial evidence that the small molecule selectively targets lysosomes. This original approach based on a fluorescent and iron-reactive probe represents a powerful strategy for initiating and, concomitantly, visualizing lysosomal dysfunction in human cells.